Evaluation of flight crew risk factors in aviation occupational health and safety: Application of Fermatean Fuzzy DEMATEL approach and machine learning - Topcu, Muhammet Bayram; Tepe, Serap; Eti, Serkan; Cabuk, Ahmet; Aslantas, Selin; Guneri, Ali Fuat (SAGE PUBLICATIONS INC, 2025)
Background Flight crews operate in an environment surrounded by a wide array of physical, chemical, biological, ergonomic, and psychosocial risks. It is inevitable that flight crews working under such challenging conditions face numerous unresolved issues, which pose significant threats to occupational safety. To prevent workplace accidents and occupational diseases in this sector, detailed studies in this area are essential.Objective Civil aviation operates on a strict timetable with no tolerance for delays, and it is a sector where the costs of errors are exceedingly high. For flight crews, who are among the most critical stakeholders in this industry, mitigating all identified risks and developing appropriate strategies incurs additional costs and processes for the organization. Therefore, it is imperative to prioritize these risks and focus on addressing the most significant ones first.Methods This study employs a novel approach and proposes a framework for identifying flight crew risk factors from an aviation safety perspective and develops the Fermatean Fuzzy Decision-Making Trial and Evaluation Laboratory (FF-DEMATEL) method to analyze the interrelationships among these factors. Study offers a comprehensive view of flight crew risk factors, facilitating decision-making and strategy development to enhance effectiveness in an uncertain and interconnected environment. The rankings of the risks were determined using the FF- DEMATEL method, with expert opinions serving as the primary data source. Expert weights were determined through machine learning based on their age, education level, and professional experience. This methodology presents a unique contribution to existing literature, offering fresh insights into this critical area of study.Results Evaluation of 11 factors reveals personnel-related risks, route-based risks and time-related risks as primary concerns, underscoring the multifaceted nature of these challenges.Conclusions To effectively control the risks in the working environment of flight crews and enhance occupational safety, it is essential to conduct detailed analyses of flight routes, increase awareness initiatives, provide comprehensive safety training, enhance improvement monitoring, and encourage the sharing of near-miss incidents.
Keywords: Fermatean fuzzy sets; DEMATEL; occupational health; occupational safety; decision-making; flight crew; civil aviation; SHIFT-WORK; SLEEP DISORDERS; ATTENDANTS; INSOMNIA; FATIGUE; BURNOUT; Public, Environmental & Occupational Health